2014
DOI: 10.1097/iae.0b013e3182a2e75d
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of the Usability of Augmented Reality Ophthalmoscopy for the Training of Inexperienced Examiners

Abstract: The study provides evidence that a single ARO training is efficient to improve ophthalmoscopy skills. As the objective analysis showed, the ARO group had a significantly superior performance. Our study also indicates that subjective evaluation of the fundus drawings without systematic analysis is prone to errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…Leitritz et al (n=37) randomized 4 th year medical students with no prior experience with BIO into control and AR groups using the EyeSI simulator. 36 All students performed the procedure the day after training and were assessed through their drawings of the patient's optic disk and arteries/veins. The AR group sketched more vessels correctly and achieved a higher Ophthalmoscopy Training Score.…”
Section: Eyesi Ar Binocular Indirect Ophthalmoscopy (Bio) Simulator (mentioning
confidence: 99%
“…Leitritz et al (n=37) randomized 4 th year medical students with no prior experience with BIO into control and AR groups using the EyeSI simulator. 36 All students performed the procedure the day after training and were assessed through their drawings of the patient's optic disk and arteries/veins. The AR group sketched more vessels correctly and achieved a higher Ophthalmoscopy Training Score.…”
Section: Eyesi Ar Binocular Indirect Ophthalmoscopy (Bio) Simulator (mentioning
confidence: 99%
“…The models, ranging from simple to complex, include an inflatable origami eye, 1 a glass marble, 2 a styrofoam head with slide projector and interchangeable lenses, 3,4 a toy eye with 90 D slit-lamp examination lens, 5 and a sophisticated computer simulation model. 6 The simpler models lack the lifelike image quality and image size found in our model, whereas the computer simulator, although quite realistic, is expensive and does not allow laser simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Leitritz et al evaluated the effectiveness of the training Eyesi indirect indirect ophthalmoscopy and concluded that there was evidence that a single training with augmented reality indirect ophthalmoscopy is effective in increasing the ophthalmoscopic skills of students (Leitritz et al, 2014). Researchers at the University of Nebraska used the EYE model and concluded that ophthalmoscopy simulation experience was able to increase the Souza P, Nunes G, Bastos J, Fonseca T, Cortizo V MedEdPublish https://doi.org/10.15694/mep.2017.000197…”
Section: Discussionmentioning
confidence: 99%